Szándékok, koncepciók az oktatás megreformálására az Oszmán Birodalomban 1839-1918 - Simonné Pallós, Piroska (Közép-Európai Közlemények, 2014)
In 1839 after Abdülmecit Sultan coming to the throne advertised a reformative adumbration composed a necssety of expansive political and socio changes (Tanzimat Fermani). The “Islahat Fermani” issued at the beginning of 1856 enforced the right assurance of the non islamic peoples lived int he Empire or enlarged their right. At the second half of the 19th century the statesmen were in Western Europe and the students learning in european schooles had have new acquaitances expedited further all comprehensive reforms, included the initiation of european type education. They were full of trust to build up social sistem will be acceptable for Europe. Than Turkey would have not been at european’s mercy nor enemy, foreign int he sight of Western Europe. What the education had been they wanted to change and how that processes were going on, what results and failers happened during that reforms trys to expose this essay.